Sustainability Analysis of Bintulu Hospital Information System Through e3value and i* Modeling - Yee Wai, Sim; Waishiang, Cheah; Bin Khairuddin, Muhammad Asyraf; Jaini, Azmi (Society of Visual Informatics, 2022)
As a pivotal supporting arm and the driving force to ensure better healthcare services, the Hospital Information System (HIS) provides the backbone support for efficiently managing the hospital's operations and services. Against the backdrop of the current economic situation and the uncertainties in the grim global economic outlook, it is crucial to optimize the cost of the information system while meeting the objectives. This paper contributes to introducing a technique to optimize the public Hospital Information System funding in Malaysia. It explores the prolonged financial viability of the HIS in Bintulu, East Malaysia, through e3Value methodology. The e3value methodology can evaluate the financial sustainability of HIS projects and can serve as a tool for early requirement analysis on future HIS deployment. From the e3value model, it is interesting to discover that actors contribute positive revenue to the hospital, allowing the hospital to generate more profit, which benefits the Government. However, actors that give negative revenue might affect future financial status. Based on the result, the recommendations presented in this paper are very crucial to ensure the continued financial sustainability of HIS. The e3value model offers early requirement study analysis and structured analysis with systematic approaches compared to the existing method. Although the work can measure the financial sustainability of the HIS, other sustainability dimensions like technological sustainability, environmental sustainability and social sustainability are yet to be explored and worth investigating in the future.